1986
DOI: 10.3733/hilg.v54n05p033
|View full text |Cite
|
Sign up to set email alerts
|

The impact of cotton plant resistance on spider mites and their natural enemies

Abstract: A spider mite-resistant and a spider mite-susceptible variety of cotton were planted in the field in a replicated design. An acaricide (dicofol) and an insecticide (acephate) were used to manipulate numbers of spider mites and their natural enemies. In general, numbers of spider mites remained low until just before midseason when 650°D air temperature had accumulated. At 650°D, mite numbers began to increase more sharply and reached significantly (P Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 57 publications
(76 reference statements)
1
12
0
1
Order By: Relevance
“…Our estimates of survival are also based on several studies showing that standard application rates of pyrethroids have minor lethal effects on spider mites (Roush and Hoy, 1978;Rock, 1979;Penman and Chapman, 1988). Low early season densities of Geocoris eggs and mobile stages of Orius, support earlier observations (Gonzalez and Wilson, 1982;Trichilo and Leigh, 1986;Wilson et al, 1991b) that in terms of density, E occidentalis is the dominant biological control agent of spider mites on cotton at this time. However, Wilson et al (1991 b) showed that even at low densities, Geocoris and Orius may be significant in delaying mid-to late-season buildup of spider mite populations.…”
Section: Model Descriptionsupporting
confidence: 70%
See 3 more Smart Citations
“…Our estimates of survival are also based on several studies showing that standard application rates of pyrethroids have minor lethal effects on spider mites (Roush and Hoy, 1978;Rock, 1979;Penman and Chapman, 1988). Low early season densities of Geocoris eggs and mobile stages of Orius, support earlier observations (Gonzalez and Wilson, 1982;Trichilo and Leigh, 1986;Wilson et al, 1991b) that in terms of density, E occidentalis is the dominant biological control agent of spider mites on cotton at this time. However, Wilson et al (1991 b) showed that even at low densities, Geocoris and Orius may be significant in delaying mid-to late-season buildup of spider mite populations.…”
Section: Model Descriptionsupporting
confidence: 70%
“…While predatory mites seem to be the primary predators of spider mites on fruit trees (Hoyt et aL, 1978;Zwick and Fields, 1978;AliNiazee and Cranham, 1980;Hull et al, 1985), the major natural enemies of spider mites on cotton in Calitbrnia, belong to a complex of generalist predators, that reach high densities in undisturbed fields (Eveleens et al, 1973;Ehler and van den Bosch, 1974;Ehler and Miller, 1978;Trichilo and Leigh, 1986). The simulations suggest that increased fecundity and shorter developmental duration make a smaller contribution to spider mite population growth on cotton, than does the loss of natural enemies, and therefore could not solely be responsible for outbreaks that were observed to occur in the field.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dit is al snel het geval bij de californische trips, Frankliniella occidentalis. Deze trips is eigenlijk een omnivoor en eet niet alleen van de plant, maar ook van dierlijke prooien (zoals spint, wittevlieg en roofmijteieren) (Trichilo & Leigh 1986;Faraji et al 2002b;van Maanen et al 2012 occidentalis (van Houten et al 1995;Messelink et al 2006). In roos, en veel andere sierteeltgewassen gaat het echter veel moeizamer dan in gewassen als komkommer en paprika (Pijnakker & Ramakers 2008 Aanvullend is bepaald wat het effect van stuifmeeltoediening op het gewas is op de bestrijding van trips met A.…”
Section: Inleidingunclassified